PKM Pendampingan Peningkatan Peran dan Fungsi Pengurus dalam Meningkatkan Pengamalan Keagamaan Santri Wilayah Zaid bin Tsabit Pondok Pesantren Nurul Jadid - Moch Tohet; Yazid Albustomi; Hosni Hosni; Muhammad Firdaws Roning; Aab Abdullah; Riduwan Hamimi; Moh Thoriq Alhakim (GUYUB: Journal of Community Engagement, 2021)
The Zaid bin Thabit area is one of the areas within the scope of the Nurul Jadid Islamic Boarding School, Paiton, Probolinggo, East Java. The situation of the students who live in the area is quite large so that the kiai's role in guiding and teaching on a daily basis cannot be fulfilled. The administrator is the kiai's long arm in guiding his students. However, the performance of the management is not maximized because there are some administrators who do not understand their roles and functions and have not been able to carry out their duties properly. While in the process of practicing religious students, of course, the role of an administrator is needed. Based on this, this program was implemented with the idea of providing knowledge and strengthening of the competence of the management, as well as experience and knowledge in order to become a professional management figure in carrying out their duties.